1995
DOI: 10.1016/1074-7613(95)90114-0
|View full text |Cite
|
Sign up to set email alerts
|

Defective B cell development and function in Btk-deficient mice

Abstract: Mutations in the Bruton's tyrosine kinase (Btk) gene have been linked to severe early B cell developmental blocks in human X-linked agammaglobulinemia (XLA), and to milder B cell activation deficiencies in murine X-linked immune deficiency (Xid). To elucidate unequivocally potential Btk functions in mice, we generated mutations in embryonic stem cells, which eliminated the ability to encode Btk pleckstrin homology or kinase domains, and assayed their effects by RAG2-deficient blastocyst complementation or intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
607
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 669 publications
(650 citation statements)
references
References 84 publications
40
607
0
3
Order By: Relevance
“…1C). As previously described [23,24], Btk-deficient mice had a specific defect in B220 high mature recirculating cells in the BM and exhibited relatively increased IgM high IgD low transitional B-cell fractions with impaired maturation into IgM low IgD high mature follicular B cells in the spleen. We have previously reported that high expression of E41K-Btk (E-Btk-3) resulted in an almost complete arrest of B-cell development at the B220 low IgM low immature B-cell stage in the BM [28].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…1C). As previously described [23,24], Btk-deficient mice had a specific defect in B220 high mature recirculating cells in the BM and exhibited relatively increased IgM high IgD low transitional B-cell fractions with impaired maturation into IgM low IgD high mature follicular B cells in the spleen. We have previously reported that high expression of E41K-Btk (E-Btk-3) resulted in an almost complete arrest of B-cell development at the B220 low IgM low immature B-cell stage in the BM [28].…”
supporting
confidence: 57%
“…Whereas in humans Btk mutations cause a severe arrest of B-cell development at the pre-B-cell stage leading to X-linked agammaglobulinemia, in the mouse there is only a mild pre-B-cell defect, differentiation of transitional into mature peripheral B cells is impaired and B-1 cells are lacking [23][24][25]. The pleckstrin homology domain mutant E41K-Btk displayed robust transformation potential in a soft-agar assay, increased membrane localization and phosphorylation in quiescent cells, independent of PI3K activity [26].…”
mentioning
confidence: 99%
“…PLCg2 À/À and BTK À/À -deficient mice have been previously described [24,43]. All animal studies were approved by the Washington University animal studies committee.…”
Section: Micementioning
confidence: 99%
“…Btk -/- [10], BLNK -/- [13], and PLCc2 -/- [17] mice on a mixed C57BL/6 Â 129 background were mated to generate Btk -/-PLCc2 -/-, BLNK -/-Btk -/-, and BLNK -/-PLCc2 -/-mice. Mice were genotyped by PCR and sacrificed if they developed signs of illness such as scruffy fur, hunched posture, lack of movement, hind limb paralysis, or visible tumors.…”
Section: Micementioning
confidence: 99%
“…A similar disease results from mutation of the human BLNK gene [9]. Mice lacking Btk [10][11][12], BLNK [13][14][15][16], or PLCc2 [17,18] have a milder phenotype with the predominant defect at the T2 to mature transition in the periphery. Btk -/-mice have a reduced frequency of Igk-expressing cells due to a role for Btk in Igk rearrangement in pre-B cells [19].…”
Section: Introductionmentioning
confidence: 99%